Technological Innovations in Forensic and Correctional Mental Health: An Introduction to the Special Issue. (February 2023) - Kirschstein, Madeleine A.; Batastini, Ashley B.; Singh, Jay P.; Graf, Marc
Although research on e-mental health in criminal justice settings continues to accumulate, the evidence base on this topic remains limited. In recent years, technological innovations have increasingly entered forensic and correctional mental health care, and the COVID-19 pandemic has accelerated their diffusion. The present special issue aims to promote evidence-based best practices and inform clinical decision-making in criminal justice settings by presenting recent developments and findings relevant to the use of e-mental health. In this introduction, we summarize the eight articles in the special issue and discuss directions for future research.